Experimental investigation of backreflection at air-core photonic bandgap fiber terminations. (1st July 2017) - Xu, Xiaobin; Yan, Ming; Wu, Chunxiao; Song, Ningfang; Zhang, Chunxi
Abstract: Backreflection from the termination of air-core photonic bandgap fibers (PBFs) is experimentally investigated based on a range-extended Mach-Zehnder and Michelson hybrid (M 2 ) interferometer. For primary waves generated by the fundamental modes, the reflectivity is about −90 dB; for secondary waves caused by other modes, the reflectivity is less than −80 dB when compared to the intensity of the primary wave and −20 to −50 dB when compared to their own incident intensity. To suppress the reflection, ~3-centimeter PBF at the end is filled with alcohol through the capillary effect, and this proposed method is shown to be much more convenient and effective than the conventional angle cleaving method. Highlights: A range-extended Mach-Zehnder and Michelson hybrid interferometer is promoted. First experimental results for mode reflectivity at flat termination of air-core PBF. First experimental result for mode reflectivity at angle-cleaved termination of PBF. Filling alcohol into the air-core PBF is proposed to suppress the backreflection.